Differential Quantitative Requirements for NPR1 Between Basal Immunity and Systemic Acquired Resistance in Arabidopsis thaliana - Ding, Yezhang; Dommel, Matthew R.; Wang, Chenggang; Li, Qi; Zhao, Qi; Zhang, Xudong; Dai, Shaojun; Mou, Zhonglin (Frontiers in Plant Science, 2020)
NPR1 (NONEXPRESSOR OF PATHOGENESIS-RELATED (PR) GENES1) is a key transcription coactivator of plant basal immunity and systemic acquired resistance (SAR). Two mutant alleles, npr1-1 and npr1-3, have been extensively used for dissecting the role of NPR1 in various signaling pathways. However, it is unknown whether npr1-1 and npr1-3 are null mutants. Moreover, the NPR1 transcript levels are induced two- to threefold upon pathogen infection or salicylic acid (SA) treatment, but the biological relevance of the induction is unclear. Here, we used molecular and biochemical approaches including quantitative PCR, immunoblot analysis, site-directed mutagenesis, and CRISPR/Cas9-mediated gene editing to address these questions. We show that npr1-3 is a potential null mutant, whereas npr1-1 is not. We also demonstrated that a truncated npr1 protein longer than the hypothesized npr1-3 protein is not active in SA signaling. Furthermore, we revealed that TGA factors are required for NPR1 induction, but the reverse TGA box in the 5’UTR of NPR1 is dispensable for the induction. Finally, we show that full induction of NPR1 is required for basal immunity, but not for SAR, whereas sufficient basal transcription is essential for full-scale establishment of SAR. Our results indicate that induced transcript accumulation may be differentially required for different functions of a specific gene. Moreover, as npr1-1 is not a null mutant, we recommend that future research should use npr1-3 and potential null T-DNA insertion mutants for dissecting NPR1’s function in various physiopathological processes.